Set-up and evaluation of a virtual test bed for simulating and comparing single- and mixed-mode ventilation strategies. (15th March 2019) - Belmans, B.; Aerts, D.; Verbeke, S.; Audenaert, A.; Descamps, F.
Abstract: Designing, optimizing and testing ventilation systems and their control strategies calls for dedicated simulation tools. Because building occupants are important influence factors for thermal comfort and indoor air quality (IAQ) and active actors by opening doors and windows, these tools must allow both an adequate modelling of air flows and of occupant behaviour. While the state of the art in software applications offers sufficient possibilities to model everyday ventilation systems, several authors indicate a need for dedicated simulation tools that enable modelling of complex mixed-mode (MMV) systems. These systems are characterised by their ability to switch between natural and (partly) mechanical operating modes according to demand and opportunity. In addition, deterministic occupant models that are often used in IAQ simulations offer room for improvement. VCVTB (Ventilation Controls Virtual Test Bed) is a new opensource EnergyPlus based test bed for single- and mixed-mode ventilation simulations, which provides a streamlined workflow for accelerated modelling, optimizing and testing of ventilation strategies and their control systems using an airflow network approach. It includes an integrated semi-probabilistic occupant model for IAQ simulation and facilitates a quick and effective comparison between systems by means of standard report sheets, comparative tables and 3D airflow output. To showcase some of the possibilities of VCVTB and to demonstrate the potential of MMV, VCVTB is used to implement a generic MMV system in a case study building. The performance of this setup is compared to several reference systems. First and foremost, the case study demonstrates the potential of VCVTB in designing and comparing ventilation strategies and their controller, facilitating further application-oriented research. Second, it shows that MMV can be a promising residential ventilation solution in regions with mild winters and cool summer. In these regions MMV can exploit the freely available natural ventilation potential to balance IAQ and adaptive user comfort with energy efficiency. Highlights: VCVTB enables accelerated modelling and testing of advanced ventilation strategies and their control systems. VCVTB facilitates application-oriented ventilation research and allows large-scale comparative studies. VCVTB avoids co-simulation by offering an integrated platform. VCVTB includes a unique semi-probabilistic model to take into account occupant behaviour in IAQ studies. Mixed-mode ventilation can be an energy friendly alternative to mechanical ventilation, but a robust control system is key.